Enhancing Students' Reading Comprehension through Reciprocal Questioning - Sari, Andini Septama; Lipta; Marlinda, Sherly (LinguaEducare: Journal of English and Linguistic Studies, 2024)
Reading has been very challenging for students especially when its position is as a foreign language. During the researchers’ observation, it was found that students’ reading scores at SMA Muhammadiyah Pagaralam are still below the standard passing score. The students expressed that it was hard for them to comprehend the reading due to their lack of vocabulary and the text was a bit difficult to understand. This study offered a method called reciprocal questioning (REQUEST) to solve that problem. This study aimed at finding out whether there was a significant difference in reading comprehension of the narrative text between the 10th-grade students of SMA Muhammadiyah Pagaralam who were taught by using the REQUEST strategy and those who were not. The method of this study is quantitative with a quasi-experiment design. Two classes were used out of six for experiment and control classes. Pre-test and post-test were used as data collection and distributed to the students in both experiment and control classes. The sample was chosen purposely non-random. Paired sample t-test and independent t-test were used to analyze the data through SPSS 22. The result of this study indicated that there was a significant difference in students’ reading comprehension.